The impact of modifiable lifestyle factors on women’s fertility - Tayyaba Shujaat; Zaheer Ahmed; Saba Liaqat (Journal of the Pakistan Medical Association)
The current study centred on assessing the effect of various lifestyle factors (diet, physical activity [PA] level, sleep pattern, and stress level) on women's fertility. This hospital-based comparative study was conducted at the Avicenna Medical College and Hospital, Lahore, Pakistan, with 104 females (aged 18-40 years) as participants. Half the participants had a history of infertility and 51.8% had a BMI >25. About 43% and 85% reported intake of “junk food” and “fruit and vegetable (F&V)”, respectively, twice a week. DASS-21 scale endorsed “moderate-to-high-stress” in 58% of the participants. Further, moderate and intense PA was documented in 30% and 20% of the participants. About 37% reported sleeping for Less-Than Or Equal To 5 hours/day. Fertility was significantly but inversely correlated with F&V intake, stress level, and BMI. Less sleep and a sedentary lifestyle had a significantly detrimental impact on fertility.